The role of serum ADAMTS-1 levels in Hyperemesis Gravidarum - Burcu Timur; Gurhan Guney (BMC, 2022)
Abstract Background We aimed to investigate the levels of ADAMTS-1, which is secreted from the extracellular matrix during trophoblastic invasion in hyperemesis gravidarum (HEG). Methods In this cross-sectional study, we compared 45 HEG patients aged between 21 and 34 in terms of ADAMTS-1 levels with a control group consisting of 44 healthy pregnant women. The demographic characteristics and several laboratory parameters of the patients were recorded. Both groups were also compared in terms of ketonuria. We evaluated the correlation between ADAMTS-1 levels and ketonuria. Results The 2 groups were matched in terms of age, gestational age, gravidity, parity, and body mass index. Some inflammatory markers, such as neutrophil count, MPV, PDW, and PCT levels, were significantly higher in the HEG groups compared to the control group (all p < 0.05). However, mean MCV and serum TSH levels were statistically significantly lower in this group (both p < 0.001). ADAMTS-1 levels were 12.6 ± 1.4 ng/ml in the HEG group and 6.2 ± 1.6 ng/ml in the control group (p < 0.001). It was significantly and positively correlated with urine ketone, neutrophil count, and PDW, whereas negatively correlated with MCV and TSH value in the HEG group. ROC analysis showed that a threshold value of 11.275 ng/ml for ADAMTS-1 predicted HEG patients with a sensitivity of 60% and specificity of 95.5%. Conclusion ADAMTS-1 serum levels are increased in HEG patients, and there is a positive correlation between ADAMTS-1 levels and ketonuria.